Integrins and p53 pathways in glioblastoma resistance to temozolomide - Dontenwill, Monique; Martin, Sophie; Janouskova, Hana (Frontiers in Oncology, 2012)
Glioblastoma is the most common malignant primary brain tumor. Surgical resection, postoperative radiotherapy plus concomitant and adjuvant chemotherapy with temozolomide is the standard of care for newly diagnosed glioblastoma. In the past decade, efforts have been made to decipher genomic and core pathway alterations to identify clinically relevant glioblastoma subtypes. Based on these studies and more academic explorations, new potential therapeutic targets were found and several targeting agents were developed. Such molecules should hopefully overcome the resistance of glioblastoma to the current therapy. One of the hallmarks of glioblastoma subtypes was the enrichment of extracellular matrix/invasion-related genes. Integrins which are cell adhesion molecules important in glioma cell migration/invasion and angiogenesis were one of those genes. Integrins seem to be pertinent therapeutic targets and antagonists recently reached the clinic. Although the p53 pathway appears often altered in glioblastoma, conflicting results can be found in the literature about the clinically relevant impact of the p53 status in the resistance to temozolomide. Here, we will summarize the current knowledge on 1) integrin expression, 2) p53 status and 3) relationships between integrins and p53 to discuss their potential impact on the resistance of glioblastoma to temozolomide.